2021
DOI: 10.1101/2021.05.24.21257744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of BNT162b2 and mRNA-1273 COVID-19 vaccines against symptomatic SARS-CoV-2 infection and severe COVID-19 outcomes in Ontario, Canada: a test-negative design study

Abstract: Objectives: To estimate the effectiveness of one and two doses of mRNA COVID-19 vaccines against symptomatic infection and severe outcomes. Design: Using a test-negative design study and linked laboratory, vaccination, and health administrative databases, we estimated adjusted vaccine effectiveness (aVE) against symptomatic infection and severe outcomes (hospitalization or death) using multivariable logistic regression. Setting: Ontario, Canada between 14 December 2020 and 19 April 2021. Participants: Commu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 36 publications
2
64
0
Order By: Relevance
“…During February-May 2021 in a multisite outpatient network evaluating COVID-19 vaccine effectiveness, vaccination reduced laboratory-confirmed symptomatic illness by 91% among those fully vaccinated and 75% among those partially vaccinated. These findings add to evidence from clinical trials of efficacy against symptomatic illness and from observational studies of vaccine effectiveness across the continuum of illness severity in multiple countries [1][2][3][4][5][10][11][12].…”
Section: Discussionmentioning
confidence: 89%
“…During February-May 2021 in a multisite outpatient network evaluating COVID-19 vaccine effectiveness, vaccination reduced laboratory-confirmed symptomatic illness by 91% among those fully vaccinated and 75% among those partially vaccinated. These findings add to evidence from clinical trials of efficacy against symptomatic illness and from observational studies of vaccine effectiveness across the continuum of illness severity in multiple countries [1][2][3][4][5][10][11][12].…”
Section: Discussionmentioning
confidence: 89%
“…Because the PLOVER database from which we sampled does not reliably capture symptoms or onset dates, we assessed VE against any infection without symptom or severity specification. VE estimates against more severe outcomes are anticipated to be higher than we report for infection per se [15][16][17]. Finally, we were limited in our ability to assess VE over the long-term or to compare to younger age groups prioritized later for vaccination, but those analyses are underway.…”
Section: Discussionmentioning
confidence: 94%
“…Using the TND to assess VE among adults ≥70 years in England (but including care-home residents), Bernal et al reported single-dose mRNA VE against symptomatic SARS-CoV-2 infection reaching 61% (95% CI 51-69) by 28-34 days[15], similar to our estimate of 69% (95% CI 59-77) by the same interval. In a matched case-control study of adults 80-83-years-old in England (excluding care-home residents), Mason ≥14 days between vaccination and specimen collection[17]. In sub-analysis of adults ≥70 years (excluding care-home residents), authors report VE of 40% (95% CI 29-49) which is lower than…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Vaccine efficacy was estimated as 95% through clinical trials (25). In the real world, it was also estimated as 46-80% for the first dose and 86-90% for the second dose (26)(27)(28)(29)(30)(31) through case-control studies or test-negative design. However, even in the real world, such studies specifically examine protection for vaccine recipients only and ignore herd immunity, representing vaccine effects on non-vaccine recipients.…”
Section: Implications Of Estimation Resultsmentioning
confidence: 99%